Pembuatan Website Company Profile sebagai Media Promosi di Sierra Adventure Malang - Raditya Abdillah Safril Pramana; Fatkhur Rochman (INDO PUBLISHING, 2025)
This study aims to develop a company profile website as a promotional medium using the WordPress CMS for Sierra Adventure Malang. The website is designed not only as an information platform but also as a strategic tool to improve the company’s image in the tourism services sector. The research employs the WebQual 4.0 framework through the action research approach, which consists of planning, implementation, observation, and reflection stages. Data collection methods included observation, interviews, and the distribution of questionnaires to 38 respondents. The instrument used to evaluate the website was based on the WebQual 4.0 model, which consists of three dimensions: usability, information quality, and interaction quality. The results of the study indicate that the website received ratings within the “strongly agree” category. The usability dimension achieved an approval rating of 91%, information quality 91%, and interaction quality also 91%. In addition, statistical data from the Jetpack plugin showed an increase in user visits and higher interaction, particularly on the homepage and product pages. In conclusion, the WordPress-based company profile website is considered effective as a promotional medium. Overall, the website is capable of presenting clear and accessible information while also supporting direct interaction with visitors.